1987
DOI: 10.1159/000205878
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Evaluation of Hydroxypyridone Iron Chelators in a Mouse Model

Abstract: The 59Fe excretion caused by a range of bidentate N-substituted [R group = methyl (CP20), ethyl (CP21), propyl (CP22), isopropyl (CP23), butyl (CP24) or hexyl (CP25)] 3-hydroxypyrid-4-one chelators in iron-overloaded mice is presented. All the compounds cause significant iron excretion when given intraperito-neally, but that the most hydrophobic compounds, CP24 and CP25, were toxic except at low doses. The excretion caused by CP21, CP22 and CP23 were significantly greater than that caused by CP20 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Although we found that CP94 was effective in the short-term treatment of gerbils, over 6 weeks, at removing iron which was being administered during the same period, the amount of iron in the heart was increased over the same period. Other short-term studies using rats and mice have also shown that the hydroxypyridin-4-ones are effective at removing hepatic tissue iron (Gyparaki et al 1987, Kontoghiorges et al 1987, Porter et al 1990, Florence et al 1992). However, rats and mice are not suitable models for prolonged iron overload as on the whole they do not respond with the same pathology as occurs in man, i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Although we found that CP94 was effective in the short-term treatment of gerbils, over 6 weeks, at removing iron which was being administered during the same period, the amount of iron in the heart was increased over the same period. Other short-term studies using rats and mice have also shown that the hydroxypyridin-4-ones are effective at removing hepatic tissue iron (Gyparaki et al 1987, Kontoghiorges et al 1987, Porter et al 1990, Florence et al 1992). However, rats and mice are not suitable models for prolonged iron overload as on the whole they do not respond with the same pathology as occurs in man, i.e.…”
Section: Discussionmentioning
confidence: 97%
“…The oral activity of a number of hydroxypyridin-4-ones has been demonstrated to be superior to DFO via the parenteral route in several shortterm animal models (26,39,48,86,118,123,127,143). As in the hepatocyte studies, compounds with intermediate lipid solubility appear to possess the optimal balance between activity and toxicity (39,50).…”
Section: Hydroxypyridinonesmentioning
confidence: 99%
“…As in the hepatocyte studies, compounds with intermediate lipid solubility appear to possess the optimal balance between activity and toxicity (39,50). Free ligands which are approximately equally soluble in lipid and water (K-part = 1) are generally the most active, whereas compounds with lipid solubilities above this are acutely toxic at relatively low doses (26,39,123). The majority of iron excretion is by the faecal route (26,123,128) and the proportion of faecal iron is highest in the more active compounds.…”
Section: Hydroxypyridinonesmentioning
confidence: 99%
“…1b. Deferiprone is water soluble and can be given orally (Hider et al 1984;Kontoghiorghes et al 1987;Gyparaki et al 1987). It possesses a pFe 3?…”
Section: Introductionmentioning
confidence: 99%